Exploring the Effects of Reviewers’ Outgroup Identity in Tourism Online Reviews: The Evidence of Perceived Intergroup Threats and Perceived Risks of Tourism Products - Liu, Yicen (Auckland University of Technology, 2024)
The tourism industry faces challenges associated with geopolitical risks (UN Tourism, 2024), which emphasise the risks associated with intergroup contact. This has the potential to negatively impact tourists' travel decision making (Lee et al., 2021). When geopolitical environments are unstable, salient information such as group identity can negatively affect intergroup perceptions. This may have negative effects on tourist attitudes towards travel destinations and host communities (Zhang et al., 2023). Travellers rely heavily on online review platforms such as TripAdvisor for pre-purchase information (Tripadvisor, 2023). Information from online reviews can reduce the uncertainty associated with tourism products before travellers experience them. Past research has shown that reviewer-related characteristics such as the ethnic identity of reviewers can positively influence readers’ perceptions of credibility and trustworthiness towards online reviews, therefore supporting tourism decision making (Lin & Xu, 2017). However, how consumers, especially ingroup consumers, perceive the outgroup identity of reviewers remains unexplored in the extant literature, including how the outgroup identity of reviewers influences tourism decision making. Especially when facing geopolitical risks in current environments, consumers may be sensitive towards information that shows group identity, which may likely activate existing perceptions regarding interactions between ingroups and outgroups. Following the integrative nature of how individuals process information in the cognitive learning process (MacInnis & Jaworski, 1989; Bohner et al., 1995), a conceptual framework is developed in this thesis to explain the effects of the outgroup identity of reviewers on consumers’ attitude formation. It proposes that pre-existing perceptions regarding the outgroup identity of reviewers and perceptions of tourism products may provide explanations for the relationship between the effects of the outgroup identity of reviewers and consumers’ attitude formation and, ultimately, their behavioural intentions. This thesis then follows this theoretical perspective to conduct one pre-test and four studies in two manuscripts to discover (1) how the salient outgroup identity of reviewers impacts tourists’ behaviour towards the tourism product, (2) whether the perception of intergroup contact and perceptions of tourism products provide explanations for the effects of the outgroup identity of reviewers on tourists’ behaviour towards the tourism product, and (3) if the outgroup identity of reviewers negatively influences tourists’ behaviour towards the tourism product, what potential solutions can reduce the negative effects of the outgroup identity of reviewers on tourists’ behaviour. Research results presented in the two manuscripts, in Chapter 3 and Chapter 4, show that the outgroup identity of reviewers is likely to increase consumers’ avoidance responses towards reviewed tourism products that are perceived to include a high level of intergroup contact. Additionally, pre-existing perceptions regarding the outgroup identity of reviewers, such as perceived threats from intergroup interactions and risk perceptions of tourism products, provide an explanation for this relationship. That is, intergroup threats drive the effects of the outgroup identity of reviewers to prompt risk perceptions of tourism products and consumers' avoidance responses towards reviewed tourism products. Decategorisation that allows group identity markers to be de-emphasized is identified as a solution to this effect. Decategorisation manipulations in tourism review sites reduce the negative effects of outgroup identity on consumers' avoidance responses towards tourism products as they lower the perceived risks of reviewed tourism products. The findings of this research contribute to research into intergroup contact in tourism, tourism online reviews, and social psychology in a tourism context. This prompts practical suggestions for travel review platforms, travel business owners, policymakers, and government-related agencies, such as reducing the presentation of group identity-related information on their online platforms.